The borrower : a novel - Makkai, Rebecca (New York : Viking, 2011)
When her favorite patron, a book-loving ten-year-old, runs away from overbearing parents who force him to attend anti-gay classes with a celebrity pastor, children's librarian Lucy Hull flees with the boy and discovers that they are being pursued by an anonymous adversary.
Keywords: Librarians -- Fiction; Boys -- Fiction; Books and reading -- Fiction; Librarians -- fiction; Boys -- Fiction; Books and reading -- fiction